THE RECENT LEGILINGUISTICS RESEARCH IN POLAND. REVIEW OF THE BOOK ENTITLED "METHODOLOGY FOR INTERLINGUAL COMPARISON OF LEGAL TERMINOLOGY. TOWARDS GENERAL LEGILINGUISTICS TRANSLATOLOGY" written by Paulina KOZANECKA, Aleksandra MATULEWSKA and Paula TRZASKAWKA. - KUBACKI, Artur Dariusz (Comparative Legilinguistics, 2018)
.